2017
DOI: 10.1103/physreve.96.062216
|View full text |Cite
|
Sign up to set email alerts
|

Crucial events, randomness, and multifractality in heartbeats

Abstract: We study the connection between multifractality and crucial events. Multifractality is frequently used as a measure of physiological variability, where crucial events are known to play a fundamental role in the transport of information between complex networks. To establish the connection of interest we focus on the special case of heartbeat time series and on the search for a diagnostic prescription to distinguish healthy from pathologic subjects. Over the past 20 years two apparently different diagnostic tec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 47 publications
7
32
0
Order By: Relevance
“…Figure 4 shows that when the non-crucial events are a form of SFBM the tail of C(t) reveals the existence of a SFBM process to the time series under study. The analysis of heartbeats of References [37,42] in addition to finding the correct crucial scaling of heartbeats, corresponding to the parameter µ slightly larger than 2, with the method of stripes, yields for C(t) the slow tail that is a signature of SFBM.…”
Section: With Stripesmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4 shows that when the non-crucial events are a form of SFBM the tail of C(t) reveals the existence of a SFBM process to the time series under study. The analysis of heartbeats of References [37,42] in addition to finding the correct crucial scaling of heartbeats, corresponding to the parameter µ slightly larger than 2, with the method of stripes, yields for C(t) the slow tail that is a signature of SFBM.…”
Section: With Stripesmentioning
confidence: 99%
“…The main theoretical result of the present paper allows us to reach some compelling conclusions about the nature of these two physiological processes. In fact, the heartbeats have been analyzed with the method of the stripes [37,42] leading the conclusion that the IPL index µ in the case of healthy individuals is close to the condition generating ideal noise, µ = 2. In a more recent paper, Bohara et al [54] using the method of the stripes analyzed the EEGs of healthy subjects in the same awake conditions as the human subjects of Reference [35] and confirmed that they have a power law index µ very close to the ideal condition µ = 2.…”
Section: Criticality and Physiological Processesmentioning
confidence: 99%
“…The stripe method was originally adopted to detect the scaling of crucial events hosted by heartbeats (Allegrini et al, 2002 ) and was not used in the case of EEG time series in all likelihood because of the lack of a proper theoretical understanding of the connection between crucial events and periodicity. The same method was more recently applied by Bohara et al ( 2017 ) to establish a connection between the occurrence of crucial events and multifractality.…”
Section: Methods Of Stripesmentioning
confidence: 98%
“…The second was based on data showing that heartbeat dynamics are a superposition of crucial and uncorrelated Poisson-like events, with patients showing a higher probability of uncorrelated Poisson-like events than healthy subjects. Increasing the magnitude of uncorrelated Poisson-like events held by heartbeats leads to a narrowing of their multifractal spectrum (Bohara et al, 2017).…”
Section: Randomness In the Human Bodymentioning
confidence: 99%